Answers

2016-04-11T20:50:09+05:30
As in the first equation there are 4 negative integers...and in the 2nd equation three negative integers.
minus *minus=positive     (even negative nos.)
minus*minus *minus=negative    (odd negative nos.)
1 5 1
2016-04-11T21:04:41+05:30
Observe the following formulas:
  (i) -  ×  - =  +
  (ii) + × + =  +
  (iii) - × + = -
  (iv) + × - = -
given,
(-9) ×(-5) ×(-6) ×(-3) = plus ×minus × minus = minus ×minus = plus
(-9) ×(-5) × 6 ×(-3)  = plus ×plus ×minus = plus × minus = minus
here, observe only the signs. that's the reason
0